Ancient bacteria of the Ötzi's microbiome: a genomic tale from the Copper Age. Issue 1 (December 2017) - Lugli, Gabriele; Milani, Christian; Mancabelli, Leonardo; Turroni, Francesca; Ferrario, Chiara; Duranti, Sabrina; van Sinderen, Douwe; Ventura, Marco
Abstract Background Ancient microbiota information represents an important resource to evaluate bacterial evolution and to explore the biological spread of infectious diseases in history. The soft tissue of frozen mummified humans, such as the Tyrolean Iceman, has been shown to contain bacterial DNA that is suitable for population profiling of the prehistoric bacteria that colonized such ancient human hosts. Results Here, we performed a microbial cataloging of the distal gut microbiota of the Tyrolean Iceman, which highlights a predominant abundance ofClostridium andPseudomonas species. Furthermore, in silico analyses allowed the reconstruction of the genome sequences of five ancient bacterial genomes, including apparent pathogenic ancestor strains ofClostridium perfringens andPseudomonas veronii species present in the gut of the Tyrolean Iceman. Conclusions Genomic analyses of the reconstructedC. perfringens chromosome clearly support the occurrence of a pathogenic profile consisting of virulence genes already existing in the ancient strain, thereby reinforcing the notion of a very early speciation of this taxon towards a pathogenic phenotype. In contrast, the evolutionary development ofP. veronii appears to be characterized by the acquisition of antibiotic resistance genes in more recent times as well as an evolution towards an ecological niche outside of the (human) gastrointestinal tract.